PUBLIKASI DAN PROMOSI NOTARIS MELALUI MEDIA ELEKTRONIK DALAM PERSPEKTIF KODE ETIK DAN PERATURAN PERUNDANG-UNDANGAN - Eka Ermala; Arga Chon Feriandref, Tri Widiastuti, Othman Ballan, Mubaraq, Duwi Aryadi (ADISAM PUBLISHER, 2024)
The purpose of this study is to find out and analyze the Perspective of the Notary Code of Ethics regarding the prohibition of Notary promotion publications through Electronic media (Internet) in the development of Technology and Information and how the legal consequences arising from violations of the Code of Ethics for the prohibition of publication and promotion of Notaries through electronic media, the provisions are in stipulate in the regulations of the Notary Code of ethics article (4) number (3) concerning the prohibition of the publication of Notary promotions in the form of advertisements, and UUJN article 17 concerning the prohibition of Notaries. so that there is a polemic that clashes between the Notary Position Act and the ITE Law where the UUJN and the Code of Ethics do not clearly and firmly regulate the limits on Promotional Publications in the form of Advertisements carried out by Notaries which can be categorized as a violation and Und The Notary Position Act seems very rigid and tarnishes the Principles and Objectives of Law Number 11 of 2008 concerning ITE and is not in accordance with the latest developments, science and technology, related to the research that the author proposes, the type of research is normative juridical. The research approach used is a research known in the Normative research method, namely the Statute Approach to examine violations of the codification of rules containing the Notary Code of Ethics, the Conceptual Approach to produce improvement concepts and the Case Approach. Approach) to examine the legal consequences of a Notary who violates the Code of Ethics. Sources of data used in this study are secondary data sources, primary and tertiary data